Antimalarial and antiplasmodial activity of husk extract and fractions of Zea mays - Jude E. Okokon; Bassey S. Antia; Dinesh Mohanakrishnan; Dinkar Sahal (Taylor & Francis Group, 2017)
Context: Zea mays L. (Poacae) husk decoctions are traditionally used in the treatment of malaria by various tribes in Nigeria. Objective: To assess the antimalarial and antiplasmodial potentials of the husk extract and fractions on malaria parasites using in vivo and in vitro models. Materials and methods: The ethanol husk extract and fractions (187-748 mg/kg, p.o.) of Zea mays were investigated for antimalarial activity against Plasmodium berghei using rodent (mice) malaria models and in vitro activity against chloroquine sensitive (Pf 3D7) and resistant (Pf INDO) strains of Plasmodium falciparum using the SRBR green assay method. Median lethal dose and cytotoxic activities against HeLa and HEKS cells were also carried out. The GCMS analysis of the most active fraction was carried out. Results: The husk extract (187-748 mg/kg, p.o.) with LD50 of 1874.83 mg/kg was found to exert significant (p < 0.05-0.001) antimalarial activity against P. berghei infection in suppressive, prophylactive and curative tests. The crude extract and fractions also exerted prominent activity against both chloroquine sensitive (Pf 3D7) and resistant (Pf INDO) strains of P. falciparum with the ethyl acetate fraction exerting the highest activity with IC50 values of 9.31 ± 0.46 μg/mL (Pf 3D7) and 3.69 ± 0.66 μg/mL (Pf INDO). The crude extract and fractions were not cytotoxic to the two cell lines tested with IC50 values of >100 μg/mL against both HeLa and HEKS cell lines. Discussion and conclusion: These results suggest that the husk extract/fractions of Zea mays possesses antimalarial and antiplasmodial activities and these justify its use in ethnomedicine to treat malaria infections.